2022
DOI: 10.3389/fmicb.2022.982109
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil bacterial communities in wheat rhizosphere to straw mulching and N fertilization

Abstract: Straw mulching and N fertilization are effective in augmenting crop yields. Since their combined effects on wheat rhizosphere bacterial communities remain largely unknown, our aim was to assess how the bacterial communities respond to these agricultural measures. We studied wheat rhizosphere microbiomes in a split-plot design experiment with maize straw mulching (0 and 8,000 kg straw ha−1) as the main-plot treatment and N fertilization (0, 120 and 180 kg N ha−1) as the sub-plot treatment. Bacterial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Our study found that the abundant bacterial phyla were similar, but their relative abundance changed in the different treatments. As in Chen et al (2022), after adding straw, the Proteobacteria , Firmicutes , Gemmatimonadota , Acidobacteriota , Bacteroidota , Actinobacteriota and Chloroflexi comprised the major part of the relative abundance in all treatments. These bacterial phyla are considered key groups in straw decomposition in soil and of great significance in carbon cycling (Banerjee et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Our study found that the abundant bacterial phyla were similar, but their relative abundance changed in the different treatments. As in Chen et al (2022), after adding straw, the Proteobacteria , Firmicutes , Gemmatimonadota , Acidobacteriota , Bacteroidota , Actinobacteriota and Chloroflexi comprised the major part of the relative abundance in all treatments. These bacterial phyla are considered key groups in straw decomposition in soil and of great significance in carbon cycling (Banerjee et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Coffee ecological recycling cultivation systems can increase the diversity and richness of the soil microbial community by enhancing soil moisture content, enhancing soil biological activity, and promoting soil mineralization and accumulation of carbon, nitrogen, and phosphorus ( Muhammad et al, 2021 ; Liu et al, 2023 ). For example, straw mulching increases the diversity and richness of the rhizosphere bacterial community by increasing the soil organic carbon (SOC) content and providing an effective carbon source for bacteria ( Chen et al, 2022 ). The mixed mulch of plastic film and straw has either a positive or negative effect on the diversity of bacteria, actinobacteria, and fungi by changing the soil temperature ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%